2014
DOI: 10.1176/appi.ps.201300206
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Justice Settings as Possible Sites for Early Detection of Psychotic Disorders and Reducing Treatment Delay

Abstract: Interventions to identify young people with untreated psychosis in jails and prisons and to refer these individuals to appropriate psychiatric care may reach some who would otherwise experience very long delays in treatment initiation. Crisis intervention team training of police officers could serve as one of several approaches for identifying these young people and diverting them into treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Other significantly and independently associated factors included recent abuse of alcohol, a history of learning disability, and presentation in mania rather than mixed episodes, depressive episodes, or non-affective psychosis. Such findings may contribute to timely identification of persons at risk of violent behavior, including in the criminal justice system, as well as in clinical settings (Noga et al 2014 ; Wan et al 2014 ; Wasser et al 2017 ), particularly with respect to first-episodes of bipolar or psychotic illness (Dean et al 2007 ; Prince et al 2007 ; Winsper et al 2013 ; Wasser et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other significantly and independently associated factors included recent abuse of alcohol, a history of learning disability, and presentation in mania rather than mixed episodes, depressive episodes, or non-affective psychosis. Such findings may contribute to timely identification of persons at risk of violent behavior, including in the criminal justice system, as well as in clinical settings (Noga et al 2014 ; Wan et al 2014 ; Wasser et al 2017 ), particularly with respect to first-episodes of bipolar or psychotic illness (Dean et al 2007 ; Prince et al 2007 ; Winsper et al 2013 ; Wasser et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of factors that predict such events may guide interventions aimed at limiting their risk. Few studies have addressed aggressive behaviors by persons diagnosed with untreated- or first-episode affective or non-affective psychotic disorders, and have considered schizophrenia more than bipolar disorder (Dean et al 2007 ; Ballester et al 2012 ; Volavka 2013 ; Winsper et al 2013 ; Wan et al 2014 ; Wasser et al 2017 ). Accordingly, we evaluated the prevalence of aggressive behaviors and their clinical and demographic correlates by first major episode in patient-subjects at first-lifetime hospitalization with a stable research diagnosis of bipolar I disorder (BD-I) with psychotic features, at 2 years of follow-up, who were enrolled and followed in the McLean-Harvard First Episode Project.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one recent study found that nearly 40% of young adults at ultra-high risk of developing psychosis had a history of violence which appeared related to high level of suspiciousness and anger on clinical review (Hutton et al, 2012). While there is an expected overlap between individuals with FEP engaging in violence and those involved with the legal system, it appears that individuals with FEP are predominantly incarcerated for non-violent offences (Cuellar, Snowden, & Ewing, 2007; Ramsay, Goulding, et al, 2011; Ramsay Wan, Broussard, Haggard, & Compton, 2014). Studies of incarceration among young adults hospitalized for FEP in an urban, low-income setting have found that more than two-thirds have been arrested and over half of individuals have been incarcerated at least once (Ramsay, Goulding, et al, 2011; Ramsay Wan et al, 2014).…”
Section: | Introductionmentioning
confidence: 99%
“…While there is an expected overlap between individuals with FEP engaging in violence and those involved with the legal system, it appears that individuals with FEP are predominantly incarcerated for non-violent offences (Cuellar, Snowden, & Ewing, 2007; Ramsay, Goulding, et al, 2011; Ramsay Wan, Broussard, Haggard, & Compton, 2014). Studies of incarceration among young adults hospitalized for FEP in an urban, low-income setting have found that more than two-thirds have been arrested and over half of individuals have been incarcerated at least once (Ramsay, Goulding, et al, 2011; Ramsay Wan et al, 2014). Similarly, studies of young adults at ultra-high risk of psychosis reported higher rates of prior arrests and convictions than the general population (Hutton et al, 2012; Purcell, Harrigan, Glozier, Amminger, & Yung, 2015).…”
Section: | Introductionmentioning
confidence: 99%
See 1 more Smart Citation